Smoking and Occupational Risks Among Traditional Divers in Lake Sentani - Medyati, Novita; Yufuai, Agustina Regina; Padang, John Toding; Ilmidin, Ilmidin (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2026)
Smoking among workers, especially traditional divers, is a factor that can contribute to health problems. This study aims to determine the perceptions and occupational risks of traditional divers regarding the activity of diving while smoking. This study is a qualitative study of traditional diver fishermen around Lake Sentani, Jayapura Regency. The research instrument was an interview guide to obtain data related to diver characteristics, smoking habits, work methods, and dive duration, as well as tools to record the interview process (tape recorder). Furthermore, the data were analyzed using Colaizzi analysis. Based on the results of the study, four main themes have been identified that describe the perception of traditional divers regarding smoking activities, namely diving as a form of assimilation of livelihood traditions to meet family food needs, consumption of hand-rolled cigarettes while diving as a function to obtain warmth and bodily pleasure, lack of knowledge and understanding of the dangers of consuming hand-rolled cigarettes while diving, and safety while diving. Kata kunci: Merokok, Penyelam, Risiko Kerja.